Ecological Study on Enrichment Planting of Shorea macrophylla (de Vriese) P.S. Ashton for Restoration of Tropical Rainforest Ecosystems in Sampadi Forest Reserve, Sarawak, Malaysia - Mugunthan, A/L Perumal (Universiti Malaysia Sarawak (UNIMAS), 2020)
Implementation of effective soil conservation management and extensive information on the soil characteristics are indispensable in order to rehabilitate and manage degraded forest land in the humid tropics of Sarawak. Better understanding and implementation of nursery cultural regimes to improve seedling quality with high survival capability and optimal growth potential are one of the pivotal aspects of a successful forest restoration program. A preliminary assessment on the status of soil morphological and physicochemical properties after the enrichment planting of one potential Bornean tropical indigenous species, Shorea macrophylla (de Vriese) P.S. Ashton in comparison to an adjacent secondary forest was conducted at Sampadi Forest Reserve, Lundu, Sarawak. The present study was also carried out to evaluate the survivorship and growth performance of S. macrophylla as well as to evaluate the effect of enrichment planting on the soil fertility status with special reference to Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF). A nursery experiment was set to determine the influences of inorganic and organic fertilisers on the morphological quality attributes of S. macrophylla seedlings in the Universiti Malaysia Sarawak nursery. Shorea macrophylla produced in the nursery and outplanted at Sampadi Forest Reserve was examined. The findings indicated that the soils in the study area consisted of mainly Grey-White podzolic soils which derived from a combination of sandstone, coarse-grained, humult ultisols, and sandy residual parent material. According to the Sarawak Soil Classification, the morphological properties resemble of Bako soil series as a dominant unit in association with Saratok series in which, corresponds to Typic Paleaquults of Soil Taxonomy by USDA-NRCS Classification. The general soil physicochemical properties indicated that the soils at reforestation sites and secondary forest were strongly acidic in nature with pH (H2O) of less than 5.5, poor in soil exchangeable bases and with low nutrient status. The soil texture was relatively of sandy clay loam to sandy clay and did not vary widely among the studied sites. Growth performance in terms of survivability; Mean Annual Increment of Height (MAIH) and Diameter (MAID) in SM96 (S. macrophylla planted in the year 1996) revealed the highest growth rate as compared to SM97, SM98, and SM99. Principal Component Analysis revealed three most significant components of the soil properties which explained 76.3% of the total variation. The first component score (PC1) was related to phosphorus content, soil acidity, and soil texture. PC2 inferred soil organic matter constituent and cation retention capacity, while PC3 related to available nutrient of the soils. Notwithstanding, a significant association was found between soil available phosphorus and S. macrophylla, indicating that soil phosphorus is a better indicator than SFI at surface soils. The findings also revealed that morphological quality attributes of S. macrophylla seedlings treated with organic jellyfish fertiliser (JF) were significantly higher (P < 0.05) than the seedlings treated with chemical fertiliser (CF) and controlled-instant release fertiliser (CIRF) at the end of nursery growing season. Older (9- and 24-month-old) S. macrophylla seedlings growth were morphologically different from younger (3- and 6-month-old) seedlings. Pooled mean survival rates overall declined from 61.7 to 44.6% after 12, 24, and 42 months of outplanting. The initial seedling age at the time of planting had significant effects on the subsequent growth performance and biomass production of seedlings. Seedling quality evaluation requires the integration of both morphological and physiological attributes of seedlings that provides a more effective appraisal of the fitness of seedlings to become established for field planting especially in the tropical forest rehabilitation area of Sarawak, Malaysia.